Establishing of irish pound - backward glance - Pratschke, Jl (Economic & Social Studies, 1969)
This paper proposes to examine the major structural developments in Irish banking during the decade of the nineteen-twenties. This was an era of great changes on the pohtical scene in Ireland, and also o f institutional changes of far-reaching significance to the Irish economy. In order to appreciate the practical problems confronting the Central Bank o f Ireland as i t exercises its role of controlling credit, it is sometimes useful to compare it with the Saorstat Eireann Currency Commission, and to note the circumstances under which the Commission was established.
Keywords: Economics; Sociology